A systematic literature review and narrative synthesis on the risk factors for developing affective disorders in open lower-limb fracture patients. (August 2022) - Abukhder, Munir; Dobbs, Thomas; Shaw, Jessie; Whelan, Rhys; Jones, Emma
Abstract: Background: Despite the advancements made in the management of the physical complications of open lower-limb fractures, few studies have been performed which investigate the association of such injuries with affective disorders. The complications resulting from this injury may result in significant psychological distress. Aim: To evaluate the risk factors associated with the development of affective disorders, in patients with open lower-limb fractures. Methods: A systematic review protocol was registered with PROSPERO and reported in accordance with the Preferred Reporting for Items for Systematic Reviews and Meta-Analyses. A comprehensive literature search was performed to gather relevant papers. Two independent reviewers screened titles and abstracts according to the inclusion and exclusion criteria. Results: 2488 were screened according to the inclusion and exclusion criteria resulting in seven articles eligible for inclusion. Of the seven articles, two assessed for PTSD, one assessed for depression and PTSD concurrently, two assessed for anxiety and depression concurrently, and two assessed for psychological distress. With the exception of two studies, open lower limb fracture patients were included with other lower-limb injuries in their analysis. Furthermore, not all variables were available in all included studies. Risk factors identified included post-operative pain, mechanism and severity of injury, age of patient, social support and social deprivation. Conclusions: Further studies are required within this area. However, addressing risk factors such as pain management, poor social support and inappropriate coping mechanisms, may reduce the incidence of affective disorders by equipping patients with necessary psychosocial resources. Highlights: Patients with strong social support have, in general, a lower risk of depression and psychological distress. Poverty is a risk factor in general for psychological distress. Negative affect may play an important role in determining physical function during the recovery period. In most patients, symptoms of psychological distress improve over time. Not all patients may display symptoms of psychological distress immediately post-injury.